Association between Cognition and Peripheral Brain-Derived Neurotrophic Factor in a Sample of Normal Adults in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Cognition is an important physiological and social element for both humans and animals. There is paucity of literature on cognitive function in Africans. Furthermore, the molecular mechanisms involved in cognition have not been fully elucidated. Brain-derived neurotrophic factor (BDNF) has a role in neuronal plasticity and cognition. However, the relationship between cognitive performance and serum BDNF levels has not been demonstrated in an African population. This study aimed to assess cognition and BDNF level and determine their relationship in a population of healthy adult Africans.Materials and Methods:Cognitive function and BDNF were determined using Mini Mental State Examination and enzyme-linked immunosorbent assay kit, respectively. SPSS statistics was used to process data.Results:Thirty male and female volunteers with a mean age of 48.7 ± 11.32 years were studied. The median cognitive score was 24.00 (21 and 28) with no sex variation (U= 107,P= 0.833). The median value of serum BDNF concentration was 2.09 ± 0.15 ng/L and statistically the same in males and females (t= 1.276,P= 0.213). Cognitive score correlated moderately with BDNF level (r= 0.369,P= 0.045), but not with sociodemographic or anthropometric characteristics.Conclusion and Recommendation:It was concluded that the population studied had normal cognitive function, which was not affected by sociodemographic and anthropometric characteristics. BDNF was a mediator of global cognitive function and was positively associated with registration and negatively associated with language domains of cognition. Peripheral levels of BDNF may potentially serve as a biomarker and index of cognitive evaluation in clinical settings.